Caliraja gen. nov., a new skate genus (Rajiformes: Rajidae) from the eastern North Pacific (Revista de Biología Marina y Oceanografía, 2022)
A new genus of skate (Caliraja gen. nov.) is described based on egg case morphology and the number of embryos per egg case. Caliraja gen. nov. egg cases differ from those of the genus Beringraja by a combination of following characteristics: egg cases relatively small in size, lacking ridges, fine striations on the capsule surface, and moderately long horns about the size of the capsule compared to the much larger Beringraja egg cases that possess distinctly prominent ridges, no striations, and short or obscure horns. The most significant difference is the new genus has a single embryo per egg case, while Beringraja have 1-9 embryos per egg case, averaging 3-5 per egg case. Evolutionarily the egg case morphology of Beringraja is more primitive than the new genus Caliraja gen. nov.